2020
DOI: 10.5406/bulcouresmusedu.226.0046
|View full text |Cite
|
Sign up to set email alerts
|

A Within-Program Analysis of edTPA Score Reliability, Validity, and Utility

Abstract: The edTPA is a multidimensional performance assessment that targets student teachers’ planning, instruction, and assessment proficiency as reflected in narrative commentary, lesson plans, teaching videos, and student work. The purpose of this study was to analyze the reliability, validity, and utility of edTPA scores for three academic year cohorts of music student teachers (N = 60) at an institution that adopted the edTPA for use in teacher candidate evaluation. Overall, music teacher candidates were rated hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Measures of internal consistency (α) in this study for all tasks and total scores exceeded .70 and were similar to those attained by Austin and Berg (2020). However, only Task 2 (Instruction, R6-R10) met the .80 benchmark for acceptable reliability while Tasks 1 (Planning, R1-R5) and 3 (Assessment, R11-R15) did not.…”
Section: Reliabilitysupporting
confidence: 73%
See 3 more Smart Citations
“…Measures of internal consistency (α) in this study for all tasks and total scores exceeded .70 and were similar to those attained by Austin and Berg (2020). However, only Task 2 (Instruction, R6-R10) met the .80 benchmark for acceptable reliability while Tasks 1 (Planning, R1-R5) and 3 (Assessment, R11-R15) did not.…”
Section: Reliabilitysupporting
confidence: 73%
“…Maybe these tasks are more closely related in music than in other subjects. However, the factor structure that emerged in Austin and Berg (2020) clearly aligned with the Planning, Instruction, and Assessment tasks, and does not support this assertion. Perhaps the teacher preparation program involved in this study taught assessment in such a way that caused students to view planning and assessment as being so closely associated that the scores they received for the a priori assessment rubrics did not coalesce in a meaningful way and, instead, loaded onto two different factors.…”
Section: Construct Validitymentioning
confidence: 79%
See 2 more Smart Citations
“…Though SCALE maintains the K–12 Performing Arts edTPA Portfolio is a performance-based measure of preservice teacher effectiveness (AACTE & SCALE, 2016), the instrument has received a considerable amount of attention and criticism regarding its validity for assessing preservice teacher readiness to enter the profession (Au, 2013; Austin & Berg, 2020; Bergstrand Othman et al, 2017; Hash, 2020; Madeloni, 2015). Researchers have indicated that university faculty feel compelled to assist preservice teachers in comprehending the numerous technical issues and portfolio criteria such as (a) page limits, (b) number of documents per task, and (c) interpretation of the handbook, rubrics, and commentaries, rather than spending more time on developing specific instructional skills (Greenblatt & O’Hara, 2015; Parkes & Powell, 2015, 2019).…”
Section: Discussionmentioning
confidence: 99%